2002
DOI: 10.1073/pnas.242377399
|View full text |Cite
|
Sign up to set email alerts
|

Increased rates of cerebral glucose metabolism in a mouse model of fragile X mental retardation

Abstract: In humans, failure to express the fragile X mental retardation protein (FMRP) gives rise to fragile X syndrome, the most common form of inherited mental retardation. A fragile X knockout (fmr1 KO) mouse has been described that has some of the characteristics of patients with fragile X syndrome, including immature dendritic spines and subtle behavioral deficits. In our behavioral studies, fmr1 KO mice exhibited hyperactivity and a higher rate of entrance into the center of an open field compared with controls, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
84
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 50 publications
18
84
0
Order By: Relevance
“…2 Similarly, whereas anxiety problems are prevalent in FXS patients, Fmr1-KO mice exhibit reduced anxiety. 8,32 Higher cognitive function is influenced by complex interactions between multiple genes. Therefore, in mouse models of inherited cognitive disorders, even subtle differences in compensatory mechanisms between humans and mice may amplify, blunt or alter the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Similarly, whereas anxiety problems are prevalent in FXS patients, Fmr1-KO mice exhibit reduced anxiety. 8,32 Higher cognitive function is influenced by complex interactions between multiple genes. Therefore, in mouse models of inherited cognitive disorders, even subtle differences in compensatory mechanisms between humans and mice may amplify, blunt or alter the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that learning may be normal, 8,30,31 mildly impaired, 7,[30][31][32][33] or even improved 34 in Fmr1-KO mice. However, there are many different types of learning, 35 and the Fmr1-KO mutation may affect some forms more than others.…”
Section: Fmr1-ko Mice Exhibit Enhanced Ppimentioning
confidence: 91%
“…Measures of learning and memory in a fear based paradigm were generally comparable for targeted and wild type alleles on a C57BL/6 background (Peier, McIlwain et al 2000), though these mice expressed reduced memory for avoidance in a leverpress paradigm compared to wild type (Brennan, Albeck et al 2006). Lack of functional FMR1 alleles on an FVB/NJ background resulted in deficits in a passive avoidance memory task (Qin, Kang et al 2002). The memory defect in gene-targeted mice C57BL/6J is not due to an FMRP-reduction of CREB, since CREB levels are comparable for targeted and wild type alleles (Li, Pelletier et al 2002).…”
Section: Fragile X Mousementioning
confidence: 90%
“…However, behavioral and physiological studies of mouse anxiety suggest abnormal, but not typically heightened anxiety responses in FMR1 knockout mice (For thorough review, see Bernardet and Crusio 2006). For example, in the FVB/NJ strain, knockout mice show reduced anxiety-related behavior in an open field test compared to wild type (Qin, Kang et al 2002). FMR1 knockouts on a C57BL/6 background, however, express heightened open field exploration and light-dark exploration relative to wild-type controls (Peier, McIlwain et al 2000).…”
Section: Fragile X Mousementioning
confidence: 99%
“…they are hyperactive), whereas mice overexpressing FMRP display hypoactivity, suggesting that FMRP acts in a dose-dependent manner [48]. Moreover, increased rates of cerebral glucose metabolism have been observed in Fmr1-knockout mice; and the regions most affected are consistent with behavioral deficiencies and regions with highest FMRP expression [49]. Recently, Drosophila has been used as a model system to explore the function of FMRP.…”
Section: Ti Bsmentioning
confidence: 99%